F-Actin is associated with a worsening qSOFA score and intensive care unit admission in emergency department patients at risk for sepsis. (3rd July 2020) - Belsky, Justin B.; Filbin, Michael R.; Rivers, Emanuel P.; Bobbitt, Kevin R.; Jaehne, Anja K.; Wisnik, Christopher A.; Maciejewski, Kaitlin R.; Li, Fangyong; Morris, Daniel C.
Abstract: Objective: We previously demonstrated that plasma levels of F-actin and Thymosin Beta 4 differs among patients with septic shock, non-infectious systemic inflammatory syndrome and healthy controls and may serve as biomarkers for the diagnosis of sepsis. The current study aims to determine if these proteins are associated with or predictive of illness severity in patients at risk for sepsis in the Emergency Department (ED). Methods: Prospective, biomarker study enrolling patients (>18 years) who met the Shock Precautions on Triage Sepsis rule placing them at-risk for sepsis. Results: In this study of 203 ED patients, F-actin plasma levels had a linear trend of increase when the quick Sequential Organ Failure Assessment (qSOFA) score increased. F-actin was also increased in patients who were admitted to the Intensive Care Unit (ICU) from the ED, and in those with positive urine cultures. Thymosin Beta 4 was not associated with or predictive of any significant outcome measures. Conclusion: Increased levels of plasma F-actin measured in the ED were associated with incremental illness severity as measured by the qSOFA score and need for ICU admission. F-actin may have utility in risk stratification of undifferentiated patients in the ED presenting with signs and symptoms of sepsis.